2013
DOI: 10.1002/hlca.201200552
|View full text |Cite
|
Sign up to set email alerts
|

Clerodendrumic Acid, a New Triterpenoid from Clerodendrum glabrum (Verbenaceae), and Antimicrobial Activities of Fractions and Constituents

Abstract: One new triterpenoid, (3β,11α,19β)‐3‐(butanoyloxy)‐11‐hydroxytaraxast‐20(30)‐ene‐23,28‐dioic acid (clerodendrumic acid; 1) was isolated from the hexane extract of the leaves of Clerodendrum glabrum var. glabrum along with heptadecanoic acid (2). The structure of the new compound was elucidated by interpretation of its NMR (1D and 2D), MS, and IR data. Combined fractions C and D from the column chromatography of the hexane extract exhibited significant antifungal activities (average MIC of 0.10 mg/ml) against C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Amusan et al [49] and Ogundajo and Ashafa [60] identified anthraquinones, cardiac glycosides, flavonoids, phenols, polyphenols, saponins, steroids, tannins and terpenoids from the leaves of V. glabra. From an extract of the leaves and stem bark of V. glabra, Fouad et al [61], Masevhe et al [62], Wanas et al [63] and Teclegeorgish [64] isolated aliphatic glycosides, iridoid, phenolics, phytosterol and triterpenoids (Table 2). Some of these chemical compounds may be responsible for the biological activities of the species.…”
Section: Nutritional and Phytochemical Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…Amusan et al [49] and Ogundajo and Ashafa [60] identified anthraquinones, cardiac glycosides, flavonoids, phenols, polyphenols, saponins, steroids, tannins and terpenoids from the leaves of V. glabra. From an extract of the leaves and stem bark of V. glabra, Fouad et al [61], Masevhe et al [62], Wanas et al [63] and Teclegeorgish [64] isolated aliphatic glycosides, iridoid, phenolics, phytosterol and triterpenoids (Table 2). Some of these chemical compounds may be responsible for the biological activities of the species.…”
Section: Nutritional and Phytochemical Compositionmentioning
confidence: 99%
“…The following pharmacological activities have been documented from the bark, fruits, leaves, roots and stems, and the compounds isolated from V. glabra: 3β-hydroxy-5-glutinene -Leaves and stem bark [64] 3β-lup-20(29)-en3-ol -Leaves and stem bark [64] Clerodendrumic acid -Leaves [62] Heptadecanoic acid -Leaves [62] Other phytochemical compounds Total flavonoid (mg quercetin/g) 22.6 -47.0 Leaves [60] Total flavanol (mg rutin/g) 17.9 -173.7 Leaves [60] Total phenol (mg gallic acid/g) 61.5 -66.0 Leaves [60] acaricidal, anthelmintic, antibacterial, antifungal, antimycobacterial, anti-collagenase, antidiabetic, antielastase, anti-inflammatory, antileishmanial, antioxidant, antiplasmodial, antipyretic, cholinesterase enzyme inhibition, immune-stimulant and cytotoxicity activities.…”
Section: Pharmacological Properties Of Volkameria Glabramentioning
confidence: 99%
See 1 more Smart Citation
“…It is occasionally grown for medical purposes in China and Vietnam and is frequently planted as an ornamental, with the double-flowered but sterile type being the most popular[42].Phytochemical screening of Clerodendrum species:[46]. Clerodendrum philippinum contains a variety of phytochemicals, including alkaloids, terpenoids, flavonoids, saponins, tannins, phenolics, and glycosides[47]. Carbohydrates, reducing sugar, hexose sugar, cardiac glycosides, saponins, tannins, and phenols were found in the hydroalcoholic extract of Clerodendrum phlomidis[48].Secondary metabolites found in abundance in Clerodendrum splendens leaves include Terpenoids, Saponins, carbohydrates, and glucosides.…”
mentioning
confidence: 99%
“…301 Ovalifolones A 556 and B 557, from Garcinia ovalifolia, 302 Clerodendrumic acid 624, from Clerodendrum glabrum, has also be reported with this stereochemistry. 337 The acetonide 625 is likely to be an artefact from chromatography of the extract of Rhododendron hainanense. 338 Ilexpublesnin F is a taraxastane saponin with a known genin from Ilex pubescens.…”
mentioning
confidence: 99%